2022
DOI: 10.3389/fpubh.2022.927338
|View full text |Cite
|
Sign up to set email alerts
|

A case report on mixed pulmonary infection of Nocardia nova, Mycobacterium tuberculosis, and Aspergillus fumigatus based on metagenomic next-generation sequencing

Abstract: BackgroundPulmonary infection is one of the common complications of long-term use of glucocorticoids. Severe infections not only increase the length of hospital stay and treatment costs but also cause progression or recurrence of the primary disease.Case descriptionHerein, we reported a case of mixed pulmonary infection secondary to glucocorticoid use. Rare pathogens such as Nocardia nova, Mycobacterium tuberculosis, Aspergillus fumigatus, and cytomegalovirus were detected by metagenomic next-generation sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…Pulmonary TB and aspergillosis have similar clinical symptoms including fever, chest tightness, shortness of breath, cough, chest pain, sputum with blood streaks, weight loss, and night sweats [ 8 ]. Therefore, they might be misdiagnosed and mistreated in clinical practice, and a definitive diagnosis relies on etiological detection results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulmonary TB and aspergillosis have similar clinical symptoms including fever, chest tightness, shortness of breath, cough, chest pain, sputum with blood streaks, weight loss, and night sweats [ 8 ]. Therefore, they might be misdiagnosed and mistreated in clinical practice, and a definitive diagnosis relies on etiological detection results.…”
Section: Discussionmentioning
confidence: 99%
“…Yan et al reported a case on mixed pulmonary infection of Nocardia nova , M. tuberculosis , and A. fumigatus based on mNGS. Although sputum and BALF were sent several times for smear and culture, only A. fumigatus was detected by culture [ 8 ]. Qin et al reported a case of mixed pulmonary infection with Corynebacterium striatum , Pseudomonas aeruginosa , Streptococcus pneumoniae , and Cryptococcus neoformans through mNGS , while microbial culture and immunological tests were all negative [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nocardia widely exists in soil, saprophytes and sewage[ 12 ]. It is an obligate aerobic bacterium with positive Gram staining and weak acid-fast staining, which usually leads to opportunistic infection[ 13 , 14 ]. The susceptible population is mainly long-term use of corticosteroids or immunosuppressants, diabetes patients and broad-spectrum antibiotic maintenance patients[ 15 - 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adult onset Still disease with steroid tacrolimus therapy Yamawaki S, [22] 2016 Drowning incident Alonso-Sierra M, [23] 2016 Ulcerative Colitis with Golimumab Therapy, mild chronic obstructive pulmonary disease, bronchiectasis and Hodgkin lymphoma Trastoy R, [24] 2017 B-cell Hodgkin lymphoma and diabetes mellitus. Dotson J, [25] 2018 Chronic Lymphocytic Leukaemia with Ibrutinib therapy Wu J, [26] 2018 Allergic bronchopulmonary aspergillosis, Repeatedly coughed up sputum for 20 y, and history of tuberculosis Matsubayashi S, [27] 2018 Severe asthma with Bronchial thermoplasty therapy and systemic steroids therapy Raj R, [28] 2020 High blood pressure, diabetes Tian X, [9] 2022 X-linked chronic granulomatous disease Roy M, [29] 2022 Systemic lupus erythematosus with hydroxychloroquine and prednisone therapy Jinlin G, [30] 2022 A Mildly Immunosuppressed Patient who had a Tooth Extraction Yan H, [31] 2022 Chronic viral hepatitis B and type 2 diabetes mellitus, highdose glucocorticoids therapy Casale TB, [14] 1984 USA/15/man Pulmonary Not available Carter JM, [15] 1990 USA/49/man Pulmonary Died Monteforte JS, [16] 1993 USA/63/man Pulmonary Recovered well Fernández Peláez JM, [2] 2000 Spain/39/man Pulmonary Died van Dam AP, [17] 2005 Netherlands/22/ man Pulmonary Recovered well Al-Anazi KA, [18] 2008 Saudi Arabia/67/ man Pulmonary Recovered well Hamadani M, [19] 2008 USA/50/woman Pulmonary Recovered well Cabada MM, [20] 2010 USA/65/man Pulmonary Recovered well Misra DP, [21] 2014 India/37/man Pulmonary Recovered well Yamawaki S, [22] 2016 Japan/84/man Pulmonary Died Alonso-Sierra M, [23] 2016 Spain/53/man Pulmonary Not available Trastoy R, [24] 2017 Spain/81/woman Pulmonary Not available Dotson J, [25] 2018 USA/64/woman Bronchopulmonary, subcutaneous tissues, lymph nodes central nervous system Died Wu J, [26] 2018 China/55/woman Pulmonary Recovered well Matsubayashi S, [27] 2018 Japan/35/woman Pulmonary Recovered well Raj R, [28] 2020 India/59/man Pulmonary Recovered well Tian X, [9] 2022 China/3/man Pulmonary, oral maxillofacial, perianal Died Roy M,…”
Section: Reference Predisposing Factorsmentioning
confidence: 99%
“…Jinlin G, [30] 2022 China/62/man Intracranial, pulmonary Recovered well Yan H, [31] 2022 China/57/Man Pulmonary Recovered well central nervous system sites. A majority (60%) of the patients demonstrated a substantial recovery posttreatment.…”
Section: Recovered Wellmentioning
confidence: 99%